2009
DOI: 10.1111/j.1600-0404.1982.tb06871.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating immune complexes and complement in the course of multiple sclerosis

Abstract: To evaluate the reactions of the humoral immune response in the course of multiple sclerosis (MS), 21 patients were examined approximately 10 times at regular intervals for 1 year. The study included concomitant investigations of the total neurological deficit (TND) and laboratory analyses of the complement profile, detection of circulating immune complexes (CIC) and heterophilic antibodies (HPA).CIC were found in 58.7 % of the investigations, often with simultaneous activation of C4 and C3. The mean values of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…These changes however were slightly below normal limits for C3, and slightly above normal limits for C4. Previous studies have shown that the mean values of the complement levels of the MS patients did not differ from the values in a normal population [20].…”
Section: Discussionmentioning
confidence: 99%
“…These changes however were slightly below normal limits for C3, and slightly above normal limits for C4. Previous studies have shown that the mean values of the complement levels of the MS patients did not differ from the values in a normal population [20].…”
Section: Discussionmentioning
confidence: 99%